The Potential of Endophytic Fungi Isolated from Leaves, Stems, Mangrove Roots Avicennia marina as a Producer of Antibiotics - Lestari, Kustiasih; Agustien, Anthoni; Djamaan, Akmal (Metamorfosa: Journal of Biological Sciences, 2019)
This study provides an overview of the potential of endophytic fungi isolated from leaves, stems, mangrove roots A. marina as a producer of antibiotics tested for Staphylococcus aureus, Escherichia coli, Candida albicans. This research was carried out in the microbiology laboratory of the Health Polytechnic of the Ministry of Health of Riau from March to June 2017. This study used a laboratory experimental method, the data presented in descriptive form. The stages of the study were: identification of A. marina plants, fungal isolation, qualitative tests of flavonoids isolates from endophytic fungal, and antibacterial activity test. The results showed that from 15 isolates of endophytic fungi, 5 isolates producing antibiotics. FAA 3 isolate showed the highest antibiotic activity with 24 mm the diameter of the inhibitory zone, while the lowest inhibition zone was FAA 4 isolate by forming a diameter of inhibitory zone of 7 mm and the results of qualitative tests of metabolites showed as secondary flvonoid metabolites. This research can be used as a source of information for the community in utilizing mangrove plants as an alternative in improving health.